2000
DOI: 10.1034/j.1399-0012.2000.140204.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycophenolate mofetil for the prophylaxis of acute GVHD in HLA‐mismatched bone marrow transplant patients

Abstract: Mycophenolate mofetil (MMF), a new immunosuppressive drug successfully used in renal and heart transplant recipients, was used in combination with cyclosporin A (CsA), methotrexate (MTX) and prednisolone for the prophylaxis of acute graft-versus-host disease (aGVHD) after bone marrow transplantation (BMT) and peripheral blood stem cell transplantation (PBSCT) from human leukocyte antigen (HLA)-mismatched, unrelated (n = 9) and related donors (n = 4) in an open single-centre phase II study. Thirteen patients, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(30 citation statements)
references
References 23 publications
1
28
1
Order By: Relevance
“…The most common adverse event in pediatric renal transplant recipients was anemia, and only a small percentage of patients developed diarrhea and leukopenia. 5 In addition MMF is used successfully for the treatment 1,2,6,7 and prophylaxis 8,9 of acute GVHD after hematopoietic stem cell transplantation. The safety profile of MMF in hematopoietic stem cell transplantation revealed 8 that the relative scores for renal, cardiac pulmonary and hepatic toxicity were comparable in the group of patients receiving MMF/CsA and those receiving MTX/CsA for the prophylaxis of GVHD.…”
Section: Departments Of Internal B Glassmentioning
confidence: 99%
“…The most common adverse event in pediatric renal transplant recipients was anemia, and only a small percentage of patients developed diarrhea and leukopenia. 5 In addition MMF is used successfully for the treatment 1,2,6,7 and prophylaxis 8,9 of acute GVHD after hematopoietic stem cell transplantation. The safety profile of MMF in hematopoietic stem cell transplantation revealed 8 that the relative scores for renal, cardiac pulmonary and hepatic toxicity were comparable in the group of patients receiving MMF/CsA and those receiving MTX/CsA for the prophylaxis of GVHD.…”
Section: Departments Of Internal B Glassmentioning
confidence: 99%
“…[10][11][12] In those studies, typically, MMF was combined with standard agents, CsA, MTX or prednisolone. [12][13][14] A prospective randomized trial in a matched sibling allo-BMT setting compared CsA and MTX with CsA and MMF showed that the incidences of grades II-IV aGVHD were 48% in the MMF group and 37% in the MTX group (P ¼ 0.49). 15 Between 1998 and 2001, several studies demonstrated safety and efficacy for MMF in GVHD therapy and prophylaxis in mismatched related or unrelated allo-HSCT.…”
Section: Introductionmentioning
confidence: 99%
“…15 Between 1998 and 2001, several studies demonstrated safety and efficacy for MMF in GVHD therapy and prophylaxis in mismatched related or unrelated allo-HSCT. [12][13][14] Although MMF has been recognized as being a very promising agent for GVHD prophylaxis, the optimal combination regimen utilizing existing drugs as well as determining the optimal time course and dose of MMF needs further investigation. To further refine the role of MMF, in June of 2001, we initiated a clinical phase I trial for a new GVHD prophylaxis regimen where CsA and MTX is combined with a short course (30 days) of low dose MMF at our institute.…”
Section: Introductionmentioning
confidence: 99%
“…18 This immunosuppressive agent might also be useful in the treatment of auto-immune diseases, such as diffuse proliferative lupus nephritis, in combination with prednisolone. 19 Preliminary clinical studies suggest that MMF might be an effective agent for prophylaxis of aGVHD 1,20,21 and/or treatment of acute 22,23 or chronic 14,22 GVHD after allogeneic BMT or PBSCT in adult patients or in children, 24 when administered alone or in combination with other immunosuppressive agents (CsA Ϯ prednisolone, 21,22 tacrolimus 14 ). However, few data are available.…”
mentioning
confidence: 99%